The Multiple Functions and Services of Community Seedbanks - Vernooy, Ronnie; Sthapit, B.R.; Galluzzi, Gea; Shrestha, P. (MDPI, 2014)
Although community-level seed-saving initiatives have existed in many countries around the world for about 30 years, they have rarely been the subject of systematic scientific enquiry. Based on a combination of a literature review and field research, we present a novel comprehensive conceptual framework that focuses on the multiple functions and services provided by community-based seed-saving efforts, in particular community seed banks. This framework is output oriented and complements an input oriented typology of community seed banks presented in 1997. The framework identifies three core functions: conserving genetic resources; enhancing access to and availability of diverse local crops; and ensuring seed and food sovereignty. The framework can be used for analysis of existing seed-saving initiatives and serve as a guide for the establishment of new community seed banks. In addition, it can inform the development or revision of national policies or strategies to support community seed banks. The framework’s utility is illustrated by three case studies of community seed banks in Bangladesh, Guatemala and Nepal.